Characteristics and prevalence of anxiety disorders, depression and somatic complaints in a 8 to 12 years old child clinical sample using the CBCL (Child Behavior Checklist) - López Soler, Concepción; Alcántara, Maria V.; Fernández, Visitación; Castro, Maravillas; López Pina, Jose A. (Anales de Psicología / Annals of Psychology, 2010)
This paper shows the internalizing symptoms: anxiety, depres-sion and somatic complaints, obtained in a clinical sample from 300 boys and girls aged between 8 and 12 years. The instrument used was the ab-breviated Child Behavior Checklist Scale (CBCL) (Achenbach & Edel-brock 1983) of 96 items. The prevalence found in the CBCL-DSM factors in the total sample, estimated from 98th percentile (Achenbach & Rescorla, 2001), is 54% in anxiety, 32% in affective alterations, and 29% in somatic complaints, finding a higher prevalence in boys than girls in the first two alterations. A factorial analysis was carried out and it was found three internaliz-ing empirical syndromes: anxious/depressed, somatic complaints and withdrawn/depressed. In these empirical syndromes the prevalence, from mean plus one SD of the sample, is: 18% in anxious/depressed and so-matic complaints, and 14% in withdrawn/depressed, and in all factors the prevalence was higher in boys than girls.